1984
DOI: 10.1177/030089168407000112
|View full text |Cite
|
Sign up to set email alerts
|

FAM2 Regimen in Disseminated Gastric Cancer

Abstract: Forty-four previously untreated patients with advanced inoperable and/or disseminated gastric carcinoma were given an i.v. combination (FAM2) chemotherapy of 5-fluorouracil, 400 mg/m2 on days 1, 2 and 3, and 21, 22 and 23; adriamycin, 40 mg/m2 on days 2 and 22; and mitomycin C, 10 mg/m2 on day 1, with a recycle on day 42 (1 cycle = 41 days). Forty patients have completed 2 cycles and are evaluable (median number of cycles 5; range 3 to 8): 26 of these achieved a partial remission, with a response rate of 65%; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1987
1987
1995
1995

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The most commonly employed combined regimen is undoubtedly the 5-fluorouracil-Adriamycin-mitomycin C (FA M ) combination, which has claimed, by its initiators, a high response rate (42%) and improved survival [19]. Others have reported a similar high re sponse rate o f 37 to 63% to F A M , with prolongation of survival in responders [3,4,10,24], However, most o f the responses were partial and o f short median duration. We have previously reported that the F A M treatment resulted in 11 (20%) complete and partial remissions in 55 patients with advanced gastric cancer with slightly insignificant prolongation o f survival in responders [13].…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly employed combined regimen is undoubtedly the 5-fluorouracil-Adriamycin-mitomycin C (FA M ) combination, which has claimed, by its initiators, a high response rate (42%) and improved survival [19]. Others have reported a similar high re sponse rate o f 37 to 63% to F A M , with prolongation of survival in responders [3,4,10,24], However, most o f the responses were partial and o f short median duration. We have previously reported that the F A M treatment resulted in 11 (20%) complete and partial remissions in 55 patients with advanced gastric cancer with slightly insignificant prolongation o f survival in responders [13].…”
Section: Introductionmentioning
confidence: 99%
“…In the 80s, after the interesting results obtained with FAM (5-FU, Adriamycin and mitomycin C) in patients with disseminated gastric cancer (42% response rate and a median survival of 13.5 months) [38], this regimen was proposed in an adjuvant setting both in the original sched ule [38][39][40] and in a modified form (FAM2) obtained by increasing drug doses and reducing the interval between cycles [41][42][43], Two studies, one in Europe (International Collabora tive Cancer Group (ICCG)) [39] and another in the USA (Southwest Oncology Group Trial) [40], have recently been completed. In neither of these studies were statisti cally significant differences found between the OS and DFS of treated patients and those of controls after median follow-ups ranging from 54 to 84 months [39,40], The ICCG demonstrated some benefit from treatment in the T3-T4 patients, but stressed the statistical bias in the ret rospective analysis of patient subgroups, and the high tox icity of this regimen [39].…”
Section: Adjuvant Chemotherapymentioning
confidence: 99%
“…Group study [85][86][87], the original FAM reg imen was modified by increasing drug doses and reducing the interval between the cycles (FAM2) [88] and was used as adju vant therapy in a controlled clinical study (Protocol No. 40813) closed to patient entry in 1989.…”
Section: Adjuvant Chemotherapy In Western Countriesmentioning
confidence: 99%